Sistem Pendidikan Pondok Pesantren Dalam Meningkatkan Life Skills Santri Pondok Di Pesantren Bustanul Ulum Al- Ghozali Jember - Firda Sari; Khoirul Anam (Lembaga Riset Ilmiah, 2022)
This study aims to describe and analyze the Islamic boarding school education system in improving the life skills of students at the Bustanul Ulum Al-Ghozali Islamic Boarding School, Dukuh Dempok village, Wuluhan, Jember. This study uses a qualitative approach to field research, data collection techniques using in-depth interviews, non participant observation and documentation studies, the collected data is interpreted from analysis using a data condensation process, data presentation and drawing conclusions. Data credibility testing technique uses triangulation of technique and time sources. The discussion un this study includes: 1) The educational system of the Bustanul Ulum Al-Ghozali Islamic boarding school supports the implementation of the lifeskills education programs for santri. 2) Life skills education integrated into curricular and extracurricular programs at the Bustanul Ulum Al-Ghozali Islamic Boarding school. 3) implication of involvement of the role a boarding school education system in the implementation of life sklls education programs.